2014
DOI: 10.1002/dta.1608
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐drug interaction and doping, part 2: An in vitro study on the effect of non‐prohibited drugs on the phase I metabolic profile of stanozolol

Abstract: The present study was designed to provide preliminary information on the potential impact of metabolic drug-drug interaction on the effectiveness of doping control strategies currently followed by the anti-doping laboratories to detect the intake of prohibited agents. In vitro assays based on the use of human liver microsomes and recombinant cytochrome P450 isoforms were developed and applied to characterize the phase I metabolic profile of the prohibited agent stanozolol, both in the absence and in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…In particular, miconazole is suspected to exert inhibitory activity on CYP450-dependent enzymes involved in steroid metabolic pathways (decrease in hydroxylated steroid formation) and on phase II metabolic conjugation with glucuronic acid. According to what in vitro demonstrated for other steroids [13,16], miconazole administration could be responsible for a decrease in Andro and Etio glucuronidation that reflects in the reduction of concentrations of these steroids in human urine.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…In particular, miconazole is suspected to exert inhibitory activity on CYP450-dependent enzymes involved in steroid metabolic pathways (decrease in hydroxylated steroid formation) and on phase II metabolic conjugation with glucuronic acid. According to what in vitro demonstrated for other steroids [13,16], miconazole administration could be responsible for a decrease in Andro and Etio glucuronidation that reflects in the reduction of concentrations of these steroids in human urine.…”
Section: Resultsmentioning
confidence: 82%
“…T glucuronide (G), AndroG, EtioG] and of the T/E ratios [38,39]. This effect was ascribed to the inhibition of the 17a-hydroxylase and 17, 20-lyase activities of CYPC17 (conversion of pregnenolone to DHEA and progesterone to ASD) [40], but recent studies have also shown its inhibitory potential on steroid glucuronidation in vitro [13,16]. Figure 1 schematizes androgen biosynthetic and excretion metabolic pathways and underlines the sites of metabolic modulations by ketoconazole and finasteride [41].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…As far as drug-drug interaction research is concerned, induction of CYP3A4 activity with DXM may lead to a more rapid metabolism of the CY3A4 target drug, in this case testosterone, reducing its half-life and, therefore, the time frame during which the drug could be detected. Inhibition of CYP3A4 activity may lead instead to an increased half-life of testosterone and therefore to an enhancement of its biological effects (Mazzarino et al 2014). This is not only true for testosterone but also for several other substances.…”
Section: Accepted Manuscriptmentioning
confidence: 98%